An Evaluation of Tourism in the Gmina of Dubeninki Using Different Research Methods - Michowiak, Anna (Turyzm/Tourism, 2004)
The article presents the spatial differentiation of tourism attractiveness in the gmiiia of Dubeninki. The author uses two basic methods: an objective ranking method, and an individualised ranking method based on the perceptions of the gmina's inhabitants and tourists. The article includes an attempt to analyse and explain the differences and similarities between the results as well an evaluation of the methods themselves